Epilepsy centers in China: Current status and ways forward. (12th September 2021) - Lin, Yicong; Hu, Shimin; Hao, Xueya; Duan, Lirong; Wang, Wei; Zhou, Dong; Wang, Xuefeng; Xiao, Bo; Liu, Xiaoyan; Wang, Yi; Zhou, Liemin; Fu, Xianming; et al.
Summary: Objective: China has the largest population of patients with epilepsy worldwide, which imposes a heavy burden on the public and health care systems. Several epidemiological surveys on epilepsy have been performed in China. Although these surveys grossly describe the prevalence and gap in treatment of epilepsy, the status of epilepsy centers is unclear. The number of epilepsy centers has increased substantially in recent decades. Therefore, a nationwide investigation of the scale and distribution, personnel, equipment, and epilepsy care capacity of each epilepsy center is of great value. Methods: In 2017–2018, a multicenter cross‐sectional survey was performed by the Commission on Standardized Development of Epilepsy Centers, China Association Against Epilepsy in 31 provinces, autonomous regions, and municipalities. The survey consisted of 74 questions divided into four sections: (1) overview, (2) personnel, (3) essential equipment and facilities, and (4) epilepsy care service capacity. The questions ranged from January 1, 2016 to December 31, 2016. The data were analyzed using descriptive statistics. Results: There were 358 epilepsy centers for the 1.38 billion national population in 2016. Three quarters were in the eastern and western regions, and >90% were in tertiary hospitals. There were 9688 doctors engaged in epilepsy care, and 4.8% of doctors and electrophysiological physicians/technicians passed the national test for electroencephalography technical accreditation. A total of 9667 patients underwent resective surgeries in 2016. There were 888 vagus nerve stimulation procedures and 275 deep brain stimulation procedures. Significance: This study is the first unique survey of epilepsy centers in China. Despite their rapid development, epilepsy centers cannot meet patients' needs at this stage. The results provide data‐based evidence for the formulation of policies related to epilepsy service planning.